﻿Craspedostauros nazmii sp. nov., a new diatom species (Bacillariophyta) from the Turkish Coast of the Black Sea - Elif Yılmaz; Andrzej Witkowski; Neslihan Özdelice; Cüneyt Nadir Solak; Romain Gastineau; Turgay Durmuş (PhytoKeys, 2023)
Craspedostauros E.J. Cox is a diatom genus comprising 17 taxa reported from various regions of the world. While many species of Craspedostauros are epibiontic, the taxa have variable ecological preferences. In this study we formally describe Craspedostauros nazmii sp. nov., an epilithic species discovered along the Turkish Black Sea Coast, based on light and scanning electron microscopy. Craspedostauros nazmii sp. nov. is characterized by valves that are lanceolate to narrowly lanceolate, slightly constricted near the apices with uniseriate, parallel throughout the whole valve, transapical striae and and the presence of an apical silica flap. The areolae are distributed over the valve face and the mantle. The differences and similarities between C. nazmii sp. nov. and established species of Craspedostauros are discussed. Based on shape and morphometrics, the most similar species is Craspedostauros capensis, but it is easily distinguished from C. nazmii sp. nov. by its lack of an apical silica flap.